Optimization Of Surface Resistivity And Relative Permittivity Of Silicone Rubber For High Voltage Application Using Response Surface Methodology - Nazir Ali, Nornazurah; Aman, Aminudin; Abd Razak, Jeefferie; Zakaria, Zahriladha; Zainuddin, Hidayat (Engineering And Scientific Research Groups, 2017)
Silicone Rubber (SiR) is considered as one of the most established insulator in High Voltage (HV) industry. SiR possess a great function ability such as its lighter weight, great heat resistance and substantial electrical insulation properties. Dynamic research were performed all around the world in order to explore the unique insulating behavior of SiR but very little are done on the optimization of SiR in term of their processing parameters and formulation. In this work, four materials and processing factors were introduced; A: Alumina Trihydrate (ATH), B: Dicumyl- Peroxide (DCP), C: mixing speed and D: Mixing time in order to analyze its contribution towards improving the surface resistivity and relative permittivity of SIR rubber. The factors range were set based on prior screening and are defined as; ATH (10 - 50 pphr), Dicumyl Peroxide (0.50 - 1.50 pphr), speed of mixer (40 - 70 rpm) and mixing period (5 - 10 mins) which were then varied accordingly to produce an overall 19 samples of SiR blends. The testing results were analyzed using statistical Design of Experiment (DOE) by applying two level full factorial from Design Expert Software (v10) to discover the inter-correlation between the factors studied and benefaction of each factor in improving both surface resistivity and relative permittivity responses of produced SiR blends The model analysis on surface resistivity shows the coefficient of determination R2 value of 88.72% while the one for relative permittivity shows R2 value of 82.34 %. Combination of both dependent variables had yielded an optimization suggestion for SiR formulation and processing strategy of ATH: 50 pphr, DCP: 0.50 pphr, mixing speed: 70 rpm and mixing period: 10 mins with the desirability level of 0.835. The optimized formulation had resulted in the production of SiR blend with the characteristic of surface resistivity of 1.02039x10-14 /sq and relative permittivity of 4.0231, respectively. In conclusion, it can be said that the materials formulation and processing parameters had significantly influenced the performance of SiR blends and thus, having the optimized material composition and processing parameters is required in producing an insulator with great function ability for high voltage application